1. The problem statement, all variables and given/known data Prove : ||V - U|| => | ||V||-||U|| | V and U are vectors 2. Relevant equations Maybe the dot product formula: ||A||*||B||cosθ 3. The attempt at a solution ==> ||V - U||2 >= (||V||-||U||)2 ==> (V-U) . (V-U) >= ||V||2 +||U||2 - 2||U||*||V|| ==> V.V + U.U -2U.V >= V.V + U.U - 2||U||*||V|| ==> -2U . V >= -2 ||U||*||V|| I don't know how to go on from here. I always get a nonsensical answer if I try to simplify this. Am I using the right approach?